The Architectural Photomontages of Piero Bottoni - Fabio Colonnese (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
Italian architects began to adopt photomontage and collage techniques only at the end of the 1920s. In the decade before the Second World War, these techniques provided architects with a visual key to distinguish themselves from the academies’ canonical representation; to seek an affiliation with the European avant-gardes; and to be recognisable in architecture competitions. They also constituted a critical tool for investigating and designing. Their peculiar evolution is exemplified in the work of the Milanese architect Piero Bottoni. Passionate about photography and cinema, Bottoni used these techniques for different purposes, not least their latent political and subversive potential, which was already implicit in the work of the artistic avant-gardes. In this sense, the analysis of some of his photomontages, which are today preserved in the Archivio Piero Bottoni (APB) at the Milan Polytechnic, reveals both his intent to introduce an anti-academic, ironic and realistic language, as well as the importance of cinema as an original source for architectural communication. Parallel to colleagues such as Giuseppe Terragni, Figini and Pollini or Ludovico Quaroni, Bottoni explored these techniques in the political context of the fascist regime, which initially promoted any kind of original artistic research; and then gradually converged towards a reactionary, conformist and populist classicism which would isolate creative voices.